The “divine comedy” of a Latin American boy: The influence of literature on Belchior's work (Revista Crioula, 2020)
This paper aims to show the influence of literature and the use of intertextual resources in the work of the Brazilian musician Belchior. Using the lyrics of all one hundred and twenty compositions recorded by the artist, combined with a brief contextualization of his professional career, it will be possible to identify and promote a reflection on the points of convergence between music and literature in the work of this renowned singer of the musical genre well known as the “Brazilian Popular Music”.